2018
DOI: 10.3201/eid2405.171192
|View full text |Cite
|
Sign up to set email alerts
|

Middle East Respiratory Syndrome Coronavirus Antibodies in Dromedary Camels, Bangladesh, 2015

Abstract: Dromedary camels are bred domestically and imported into Bangladesh. In 2015, of 55 camels tested for Middle East respiratory syndrome coronavirus in Dhaka, 17 (31%) were seropositive, including 1 bred locally. None were PCR positive. The potential for infected camels in urban markets could have public health implications and warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 10 publications
2
24
0
1
Order By: Relevance
“…Several studies found imported animals to have significantly higher seroprevalence than their locally bred counterparts (22, 25, 29, 30). Dromedaries sampled at markets, abattoirs and quarantine sites had higher seroprevalence than those in farms, villages and research facilities (22, 29, 30, 39). In some cases, dromedary origin varied with the type of site sampled suggesting confounding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies found imported animals to have significantly higher seroprevalence than their locally bred counterparts (22, 25, 29, 30). Dromedaries sampled at markets, abattoirs and quarantine sites had higher seroprevalence than those in farms, villages and research facilities (22, 29, 30, 39). In some cases, dromedary origin varied with the type of site sampled suggesting confounding.…”
Section: Resultsmentioning
confidence: 99%
“…See Fig 4 for a map of RNA prevalence, and Table 1). Despite moderate seropositivity, surveys have not detected active MERS-CoV infection in the dromedary populations of Bangladesh or Israel (22, 35).…”
Section: Resultsmentioning
confidence: 99%
“…4 for a map of RNA prevalence, and Table 1). Despite moderate seropositivity, surveys have not detected active MERS-CoV infection in the dromedary populations of Bangladesh or Israel (David et al, 2018;Islam et al, 2018). RNA prevalence in dromedary populations linked to human cases was similar to more randomly sampled populations in the same country, with the exception of two small outbreak studies in the UAE which found 100% of epidemiologically linked dromedaries to be infected (Al Hammadi et al, 2015;Paden et al, 2018).…”
Section: Prevalence Of Active Mers-cov Infection -Cross-sectional Stumentioning
confidence: 92%
“…Several studies found imported animals to have significantly higher seroprevalence than their locally bred counterparts (Gutierrez et al, 2015;Ali et al, 2017a, b;Islam et al, 2018). Dromedaries sampled at markets, abattoirs and quarantine sites had higher seroprevalence than those in farms, villages and research facilities (Ali et al, 2017a, b;van Doremalen et al, 2017;Islam et al, 2018). In some cases, dromedary origin varied with the type of site sampled suggesting confounding.…”
Section: Sample Population Characteristicsmentioning
confidence: 99%
“…Dromedary camels, bats, and other animals are potentially involved in MERS-CoV transmission [1,12,35,42,60]. Antibodies against MERS-CoV in domestic livestock (including dromedary camels) in the Middle-East and Africa were investigated using ppNT, MN, and IFA assays [7,27,29,[34][35][36]48,53,60,70]. MERS-CoV IgG seropositivity gradually increased in dromedary calves from the Middle East with increasing age based on the S1-ELISA.…”
Section: Discussionmentioning
confidence: 99%